Studi Kualitas Energi Listrik Gedung Fakultas Teknik Universitas Bangka Belitung - Asmar Asmar; Wahri Sunanda (Fakultas Teknik, 2021)
One of the performances of the electric power system can be seen from the quality of electrical energy. In this study, the measurement of the quality of electrical energy was carried out using a power quality meter to obtain the values of current, voltage, frequency, total current harmonic distortion and total voltage harmonic distortion in the building of the Faculty of Engineering, Universitas Bangka Belitung. From measurements on the 3 existing buildings, it was found that the measured voltage value range was still at + 5% to - 10% of the 220 Volt secondary distribution voltage value and the frequency value was still in the range of 49.5 Hz to 50.5 Hz. The total value of voltage harmonic distortion is still below the required value, but the total value of current harmonic distortion is above the required value.